PENGEMBANGAN KINERJA DOSEN FAKULTAS USHULUDDIN IAIN AR-RANIRY BANDA ACEH - Hambali .; Cut Zahri Harun; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Lecturer has a crucial position in the process of education, lack of lecturers’ performance in carrying out the assignment will result in the quality of graduates, and the development of lecturer performance to increase the high-quality graduates is absolute to be prioritized. This study aims to find out program, the implementation and the supporting of developing lecturer performance, in “Tridarma Perguruan Tinggi”. This study used descriptive qualitative research methods. Subject of the study is Dean, Assistant Dean and chairman of department. The technique of data analysis is done by data reduction, data presentation, drawing conclusions and verification. The study result: (a). Sector of education and teaching further education maintain lecturer rank, revise syllabus, cooperate with other universities, and doing monthly discussion, (b). Sector of research conducted lecturer training and scientific writing competition, (c). Sector of Community Service: founding model village, religious speaker, khatib of Friday prayers, supervisor of community service activity. The implementation of the lecturer development program of the Ushuluddin Faculty in the case of education and teaching run asprogrammed, as well as the research. While in the case of community service institutionally is not maximal yet, even that individually lecturer at the Ushuluddin Faculty performs community service. The factors developing lecturer performance both master and bachelor and office infrastructure, facilitation, classroom and Ushuluddin Faculty also have its own publishing house, they are: Publishing and two scientific journals; Substantia and Al-Mu'asirah, in which it support the lecturers in developing the performance.Keywords : Development of lecturers’ performance